Conditional Cash Transfer in the Philippines: How to Overcome Institutional Constraints for Implementing Social Protection. Issue 1 (January 2015) - Kim, Eunju; Yoo, Jayoung
Abstract: This article explores how global social policy can be implemented in the local context by examining the policy process undertaken for the conditional cash transfer program (CCT) in the Philippines. It first takes into consideration how they select CCT as flagship social protection program. It, furthermore, takes an in‐depth look at the policy implementation process to find out how the Philippines overcomes institutional constraints where clientelism is prevalent and administrative capacity is inadequate. It shows that CCT could be implemented by centralising targeting and delivery system, investing financial resources with political commitment of national government, and rearranging responsible department based upon inter‐ministerial cooperation. Even though administrative set‐up has been singled out as the principal obstacle hindering necessary policy change in developing countries, this article maintains that the administrative capability can be enhanced in the process of implementing social protection programs.